Determination of Stress Intensity Factor for Arc-shaped Tension Specimen by Using Finite Element Analysis - Marjono, Nurulain (Universiti Teknologi Petronas, 2008)
Fracture mechanics is a method for predicting failure of a structure containing a crack which divided into linear elastic fracture mechanics and nonlinear fracture mechanics. The most important parameter in fracture mechanics, Stress Intensity Factor (SIF), K, is used to more accurately predict the stress intensity near the tip of a crack caused by a remote load or residual stresses. Fracture Toughness, Kc is a property which describes the ability of a material containing a crack to resist fracture when load is applied to the material. Fracture occurs when K1 ~ Kc. The crack tip parameter K is useful tool to calculate the crack growth up to fhllure for different crack geometry and loading conditions. The advancement of finite element source codes allows the crack tip parameters (SIF and stress distribution) to be computed nearly accurate without being overly dependent on purely experimental work which is time and cost consuming. The aim of the present work is to investigate the SIF of Mode-I crack type specimen used in general applications. The SIF for different loading value and varied parameter which obtained from ANSYS software will be analyzed and compared with the calculation method. The modeling work is carried out using Arc-shaped Tension specimens. In this study, the Arc-shaped Tension specimen was modeled to carry aluminum properties, which exhibit linear-elastic behavior under stresses. This specimen was modeled to be plane-strain and finite-width exerted with opening mode loading (Mode-l). The ANSYS finite element software is employed to model this specimen and obtain the value ofSIF to compare and validate through theoretical calculation. The modeling results have exhibit proper linear-elastic behavior and stress distribution. From the numerical data and theoretical considerations, it shown that the Mode-l SIF are dependent of the loading applied to the specimens. All of all, the results show that increasing the load applied, ring segment distance, crack length or decreasing the thickness can significantly increase the SIF.